Sticks, Stones, and Broken Bones: Protest Violence and the State. (March 2019) - Sullivan, Heather
From armed-building occupations to fisticuffs between protesters and police at otherwise peaceful demonstrations, protest violence is an essential part of the politics of protest. In this article, I argue that state capacity is central to understanding why some protests are violent. In particular, this article explores two facets of state capacity—coercive capacity and state authority—arguing that where the state is treated as a relevant authority, the likelihood that protesters will employ violent tactics decreases. Using original data on Mexican protest events, I demonstrate that higher levels of state authority reduce violent protest but that increased coercive capacity, especially where state authority is weak, is associated with a greater likelihood of protest violence. This article contributes to our understanding of the influence of state capacity on protest violence and suggests that attentiveness to subnational variations in state capacity can help us better understand the violence.